Factors That Influence Optimization Open Space Under the Jenggolo Sidoarjo Flyover - S H Laksono; V G Paryoko (Institut Teknologi Sepuluh Nopember, 2018)
Population in Surabaya and Sidoarjo grows rapidly every year. The need for open space is increasing from the needs of residences, shops, hotels, malls, and so on, so that almost every open space in every area is utilized both by legal buildings and illegal buildings or activities. The emergence of illegal activities in areas that are not utilized such as commensurate environmental lines, under flyovers, and around the banks of rivers, can cause the growth and structuring of the city to be hampered. The location of this research paper is under the Jenggolo Sidoarjo flyover, and it is known that there is an irregularity in the arrangement of both street vendors, open spaces, parks and there is still plenty of free space on the site. So as to support the government's efforts in correct and optimal spatial planning and cities. The paper that will be discussed is how to know the potential and ways to develop existing potentials into a public space that is sensitive to public and surrounding environment. So that the public space created is expected to be able to support the arrangement of space and the city of Sidoarjo in particular.